Remotely controlled crawler for underwater inspection - Teoh, Boon Siew (2018)
The main objective of the “Remotely controlled crawler for underwater inspection” project is to develop and construct a fully automotive ROV-attachable tool for underwater inspections. Robotic tools are installed on the crawler which includes the hardware and software of it (movement control and positioning). The main improvement in this project is to integrate the scanning probe onto the crawler and use it to locate the defects during an inspection on wet condition (Object of inspection is fully submerged in water). Object of inspection is chosen to be steel pipe which is widely used across the world. Other improvements to the crawler are to have more efficient post processing software to help facilitate the data after inspection. The design requirement for the hardware aspect is to incorporate a fixture for the scanning probe on the crawler. The final design will be created through a series of technical design procedure and will be able to achieve the required scanning process during inspection. While the project manages to fulfil its objective, there will be room for improvements which will be discussed in this paper.